The application of the quick response manufacturing system (QRM) in Sudanese industrial companies and its impact on reducing costs and achieving competitive advantage (For the period 2017-2022) (Analytical study) - Almekki, Amira Abdalrhman (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to shed light which the quick response manufacturing system (QRM) can be applied in Sudanese industrial companies and its impact on reducing costs and achieving competitive advantage by reducing lead times and deleting activities that do not add value and the consequent reduction in cost and speed in completing production processes and work orders In general which leads to gain customers confidence in the price and quality of products and thus increasing the competitive advantage. The research objective identifies the methods and elements of the quick response manufacturing system which are used to influence cost reduction and achieve a competitive advantage in Sudanese industrial companies. The researcher has used the deductive approach when choosing a problem, the study and the development of scientific hypotheses. In addition to, the statistical analysis that has relied on the field study. The study population and sample consist of a group of accountants, production managers, engineers and technologists. The most important results By testing the hypotheses of the study, it was found that the value of the (t) test is )23.847( with a degree of freedom of 102 and a significant level (0.000), which indicates a statistically significant relationship between the Sudanese companies’ application of the quick response manufacturing system and cost reduction and an increase in competitive advantage by 95%. This means that the Sudanese industrial companies that applied this system during the study period achieved a cost reduction and that the speed of their response by increasing their market share of products leads to attracting new customers, thus achieving a competitive advantage in the local and global markets.. The study has recommended that Sudanese industrial companies adopt the quick response manufacturing system as a comprehensive applied strategy that includes an intellectual tendency that seeks to severely and continuously reduce production deadlines and develop scientific competence and skills by urging with industrial company managers’ and production managers to participate in conferences and seminars held by professional people related to the quick response manufacturing system.